PROBING OF 1/2 ORDERING IN BA(NI1/3NB2/3)O-3 AND BA(ZN1/3NB2/3)O-3 CERAMICS BY XRD AND RAMAN-SPECTROSCOPY - KIM, BK; HAMAGUCHI, H; KIM, IT; HONG, KS (AMER CERAMIC SOC 735 CERAMIC PLACE, 1995)
The 1:2 ordering in Ba(Ni1/3Nb2/3)O-3 ceramics sintered at 1350 degrees-1500 degrees C has been investigated by using XRD and Raman spectroscopy. Both of the techniques show that the degree of the 1:2 ordering decreases as the sintering temperature increases, However, XRD discerns the 1:2 ordering only for the samples sintered at 1350 degrees-1400 degrees C, whereas Raman spectroscopy discerns the 1:2 ordering for all the samples. Similar results have been obtained for Ba(Zn1/3Nb2/3)O-3 ceramics, where only the temperature range is slightly different. It is demonstrated that Raman spectroscopy can be a useful tool for probing of the 1:2 ordering in the A(B'B-II(1/3) ''(V)(2/3))O-3-type complex perovskite compounds.
Keywords: FERROELECTRICS